2020
DOI: 10.1158/1078-0432.ccr-19-1868
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived CXCL9 and CXCL10 Are Required for Antitumor Immune Responses Following Immune Checkpoint Blockade

Abstract: Purpose: Response rates to immune checkpoint blockade (ICB; anti-PD-1/anti-CTLA-4) correlate with the extent of tumor immune infiltrate, but the mechanisms underlying the recruitment of T cells following therapy are poorly characterized. A greater understanding of these processes may see the development of therapeutic interventions that enhance T-cell recruitment and, consequently, improved patient outcomes. We therefore investigated the chemokines essential for immune cell recruitment and subsequent therapeut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
347
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(380 citation statements)
references
References 81 publications
(100 reference statements)
32
347
1
Order By: Relevance
“…It has been proven that CXCL10 could attenuate the process of new vessel formation and lead to reduced tumor growth in multiple human cancer models, such as non-small-cell lung cancer, colon-rectal cancer [111,112]. In addition, data derived from studies in other human malignancies suggested that this antitumor effect is mainly through the regulation of immune response, currently available evidence indicates that (i) CXCL10 attracts CD8+ and CD4+ effector T cells to tumor sites and sites of inflammation [113], (ii) CXCL10 stimulates immune cells through Th1 polarization and activation [114,115], (iii) CXCL10 are indispensable for robust responses to immune checkpoint inhibitors (anti-PD-1 and anti-CTLA-4) and improves therapeutic efficacy of radiotherapy [116,117].…”
Section: Renal Cell Carcinoma (Rcc)mentioning
confidence: 99%
“…It has been proven that CXCL10 could attenuate the process of new vessel formation and lead to reduced tumor growth in multiple human cancer models, such as non-small-cell lung cancer, colon-rectal cancer [111,112]. In addition, data derived from studies in other human malignancies suggested that this antitumor effect is mainly through the regulation of immune response, currently available evidence indicates that (i) CXCL10 attracts CD8+ and CD4+ effector T cells to tumor sites and sites of inflammation [113], (ii) CXCL10 stimulates immune cells through Th1 polarization and activation [114,115], (iii) CXCL10 are indispensable for robust responses to immune checkpoint inhibitors (anti-PD-1 and anti-CTLA-4) and improves therapeutic efficacy of radiotherapy [116,117].…”
Section: Renal Cell Carcinoma (Rcc)mentioning
confidence: 99%
“…Then, 908 DEGs (900 upregulation and eight down-regulation) were screened from the immune score and stromal score based on the ESTIMATE algorithm [8]. [18,19]. CXCR3, the receptor for CXCL9 and CXCL10, is highly expressed on CD8 + and CD4 + immune-in ltrating lymphocytes, it is highly likely that local production of CXCL9/10 can modulate T-cell recruitment and activation in human cancers [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…[18,19]. CXCR3, the receptor for CXCL9 and CXCL10, is highly expressed on CD8 + and CD4 + immune-in ltrating lymphocytes, it is highly likely that local production of CXCL9/10 can modulate T-cell recruitment and activation in human cancers [18][19][20]. These chemokines are increased following expose to anti-PD-1 and that they are crucial for therapeutic activity and correlate with patient prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL9, CXCL10 exert their function through binding to C-X-C motif receptor CXCR3 that was highly expressed on the activated T cells [30]. Research shows that CD8 + T cell in ltration is CXCR3 dependent [38]. CD8 + T cell plays important role in tumor microenvironment, which inhibits the proliferation and metastasis of tumor cells.…”
Section: Moreover Skcm Patients With High Expression Of Ve Chemokinementioning
confidence: 99%